2005
DOI: 10.1098/rsbl.2005.0398
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and the evolution of female resistance to remating in seed beetles

Abstract: Female remating behaviour is a key mating system parameter that is predicted to evolve according to the net effect of remating on female fitness. In many taxa, females commonly resist male remating attempts because of the costs of mating. Here, we use replicated populations of the seed beetle Acanthoscelides obtectus selected for either early or late life reproduction and show that 'Early' and 'Late' females evolved different age-specific rates of remating. Early females were more likely to remate with control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
0
21
1
Order By: Relevance
“…This assumption may require some defending, given that there is ample evidence that females can become unreceptive after a mating (e.g., Teuschl & Blanckenhorn, 2007), or adjust their choosiness depending on their age (Moore & Moore, 2001;Maklakov et al, 2006) or mating history (e.g., Pitcher et al, 2003;Fitze et al, 2010; for theory see Kokko & Mappes, 2005;Bleu et al, 2012). To keep the model as close to a 'null' as possible, we assumed no plastic behaviour based on mating history or their own past frequency of mate encounters.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption may require some defending, given that there is ample evidence that females can become unreceptive after a mating (e.g., Teuschl & Blanckenhorn, 2007), or adjust their choosiness depending on their age (Moore & Moore, 2001;Maklakov et al, 2006) or mating history (e.g., Pitcher et al, 2003;Fitze et al, 2010; for theory see Kokko & Mappes, 2005;Bleu et al, 2012). To keep the model as close to a 'null' as possible, we assumed no plastic behaviour based on mating history or their own past frequency of mate encounters.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not know if (i) older females had intrinsic characteristics that make them less receptive with age, (ii) older females have lower thresholds to resist male manipulation, or (iii) males invest more in inhibiting remating of older females. Maklakov et al (2006) demonstrated that females of the seed beetle Acanthoscelides obtectus selected for early reproduction had increased remating rates as they aged, while females selected for late reproduction had decreased remating rates later in life. In A. fraterculus, females with higher fecundity also have higher remating rates while those with lower fecundity have lower remating rates (Abraham et al 2011).…”
Section: Female Remating Behaviormentioning
confidence: 98%
“…We also found that the reproductive behavior of females and males was changed in the E and L populations. Early‐life mating frequencies and mating speed of both sexes, as well as females’ re‐mating rates, were substantially higher in the late‐reproducing populations rather than in the early‐reproducing populations (Maklakov et al. 2006; Šešlija et al.…”
Section: Introductionmentioning
confidence: 98%